Samoorganizacja procesu kształcenia studenta - Zinowiew, Igor Feliksowicz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
W artykule autor porusza kwestie związane z samodzielną organizacją pracy naukowej studentów. Zauważa, iż skuteczność procesu nauczania na szczeblu wyższym zależy w dużej mierze od umiejętności studentów do samodzielnej pracy z podręcznikami i materiałami naukowymi. Obok teoretycznego podejścia do samoorganizacji procesu kształcenia, wymienione są takŜe przeszkody i trudności zakłócające ten proces.

In the paper the author takes into consideration some issues connected with an individual organising of educational work of students. He indicates that efficiency of the education process at tertiary level depends mainly on students’ abilities to work individually with handbooks and educational materials. Beside a theoretical approach to self-organising the educational process, there are also pointed out some barriers and difficulties that disrupt this process.
Self-Organising the Process of Students' Education